The Regional Western Sweden SOM Survey 1996 - SOM Institute, University of Gothenburg (University of Gothenburg, 1998)
This is the fifth study in the series of SOM-surveys carried out in Western Sweden exclusively. The questionnaire was divided into six subject fields: mass media; politics and society; the municipality of Göteborg; traffic and environment; leisure; and background. Most of the questions are replications of questions asked in one or several previous SOM-surveys. New media questions dealt with thoughts of giving up morning paper subscription, and habits concerning television viewing. Other questions focused on the respondent´s opinion on the function of democracy in Sweden as well as in their own municipality; possibilities to influence a number of local government activities, and if the respondent had tried to influence local government activities during the last year. Respondents also had to state if they believed one in general can trust most people, and how satisfied they were with their own life. A number of questions dealt with the importance of different education and research areas on the future development of Göteborg and the Göteborg region, and the respondent´s contacts with different educational organizations in Göteborg. The respondents also had to give their opinion on the traffic situation in Göteborg. Furthermore they had to report about membership and activities in different organizations. The respondents also had to indicate if they, or someone in their family, had been affected by the tightening labour market. They also had to give their opinion on the future possibilities for children and youth of today to get a good education, employment, good housing, and the same welfare as today.

Purpose:

Study attitudes and behaviors that are linked to local and regional issues and phenomena

Detta är den femte studien i serien SOM-undersökningar genomförda i Västsverige. Brevenkäten var indelad i sex frågeområden: Massmedier; Politik och samhälle; Göteborgs kommun; Trafik och miljö; Fritid; samt Bakgrundsfrågor. Personer bosatta i Göteborgs kommun fick även ange inställning till åtta kommunala politiker samt om man känner till vilken stadsdelsnämnd man tillhör. De flesta frågorna är ställda i en eller flera tidigare Väst-SOM. Nya frågeställningar i 1996 års undersökning tar upp: tankar på att upphöra med tidningsprenumeration; vanor när det gäller TV-tittande; inställning till hur demokratin fungerar i Sverige som helhet samt i den egna kommunen; vilka möjligheter man anser sig ha att vid behov påverka verksamheten inom: hälso- och sjukvård, barnomsorg, skola, äldreomsorg, fritid/kultur, planfrågor och socialtjänsten; om man försökt påverka någon kommunal eller landstingskommunal verksamhet senaste året. Respondenten fick även ange i vilken utsträckning det går att lita på människor i allmänhet samt hur nöjd man är med det liv man lever. Ett antal nyinsatta frågor behandlade hur viktigt man ansåg olika satsningar på utbildnings- och forskningsområden är för Göteborgs och Göteborgsregionens framtida utveckling, samt om responden genom studier/arbete eller på något annat sätt kommit i kontakt med Chalmers, delar av Göteborgs universitet eller annan utbildningsorganisation. Respondenter bosatta i Göteborgs kommun fick ta ställning till ett antal påståenden om trafiksituationen i Göteborg. Därutöver ställdes frågor om medlemskap och aktivitet i olika föreningar. Respondenterna fick även ange om de själva eller någon familjemedlem drabbats av det försämrade läget på den svenska arbetsmarknaden. Avslutningsvis fick man bedöma möjligheterna för dagens barn och ungdomar att i framtiden kunna få god utbildning, fast anställning, bra bostad och samma välfärd som idag.

Syfte:

Studera attityder och beteenden som är knutna till lokala och regionala frågor och företeelser
Den västsvenska SOM-undersökningen 1996
Väst-SOM 1996
Keywords: housing; boende; mass media; massmedia; public sector; offentlig sektor; political interest; politiskt intresse; local government services; kommunal service; public services; offentlig service; internal politics; inrikespolitik; political parties; politiska partier; politicians; politiker; leisure time activities; fritidsaktiviteter; mass media use; mediaanvändning; CORS; CORS; Media; Media; Environment and conservation; Miljö och naturvård; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap